A down-shifting Eu3+-doped Y2WO6/TiO2 photoelectrode for improved light harvesting in dye-sensitized solar cells. Issue 2 (7th February 2018) - Llanos, J.; Brito, I.; Espinoza, D.; Sekar, Ramkumar; Manidurai, P.
Abstract : Y1.86 Eu0.14 WO6 phosphors were prepared using a solid-state reaction method. Their optical properties were analysed, and they was mixed with TiO2, sintered, and used as a photoelectrode (PE) in dye-sensitized solar cells (DSSCs). The as-prepared photoelectrode was characterized by photoluminescence spectroscopy, diffuse reflectance, electrochemical impedance spectroscopy (EIS) and X-ray diffraction. The photoelectric conversion efficiency of the DSSC with TiO2 :Y1.86 Eu0.14 WO6 (100:2.5) was 25.8% higher than that of a DSCC using pure TiO2 as PE. This high efficiency is due to the ability of the luminescent material to convert ultraviolet radiation from the sun to visible radiation, thus improving the solar light harvesting of the DSSC.